Individual and neighborhood socioeconomic status and progressive chronic kidney disease in an elderly population: The Cardiovascular Health Study. - Merkin, Sharon Stein; Diez Roux, Ana V; Coresh, Josef; Fried, Linda F; Jackson, Sharon A; Powe, Neil R (Soc Sci Med, 2007)
Few studies have focused on the association between socioeconomic status (SES) and progressive chronic kidney disease (pCKD) in an elderly population. We conducted a cohort study of 4735 Cardiovascular Health Study participants, ages 65 and older and living in 4 US communities, to examine the independent risk of pCKD associated with income, education and living in a low SES area. pCKD was defined as creatinine elevation 0.4 mg/dL (35 micromol/L) over a 4-7 year follow-up or CKD hospitalization. Area SES was characterized using measures of income, wealth, education and occupation for 1990 (corresponding to time of enrollment) US Census block groups of residence. Age and study site-adjusted incidence rates (per 1000 person years) of pCKD by quartiles of area-level SES score, income and education showed decreasing rates with increasing SES. Cox proportional hazards models showed that living in the lowest SES area quartile, as opposed to the highest, was associated with 50% greater risk of pCKD, after adjusting for age, gender, study site, baseline creatinine, and individual-level SES. This increased risk and trend persisted after adjusting for lifestyle risk factors, diabetes and hypertension. We found no significant independent associations between pCKD and individual-level income or education (after adjusting for all other SES factors). As such, living in a low SES area is associated with greater risk of pCKD in an elderly US population.
Keywords: Age Factors; Aged; Cohort Studies; Female; Humans; Incidence; Kidney Failure, Chronic; Male; Proportional Hazards Models; Residence Characteristics; Risk Factors; Sex Factors; Social Class; United States